A Systematic Literature Review on Salvage Radiotherapy for Local or Regional Recurrence After Previous Stereotactic Body Radiotherapy for Lung Cancer - Matsuo, Yukinori (Technol Cancer Res Treat, 2018)
PURPOSE: The purpose of this review article was to summarize available data on the efficacy and safety of salvage radiotherapy for isolated local or regional recurrence after prior stereotactic body radiotherapy for lung cancer. METHODS: Studies were systematically searched on PubMed, following which suitable papers were selected. Reported outcomes and toxicities were qualitatively reviewed. RESULTS: Nineteen papers, which were retrospective studies based on single institution experiences, were selected. Sixteen papers were on salvage radiotherapy for local tumor recurrence, and the remaining 3 papers evaluated radiotherapy for regional failures after stereotactic body radiotherapy for lung cancer. Patient cohorts in the selected papers seemed very frail with 2-year survival of 30% to 40% after the salvage. Local control was reported to be approximately 60% to 70%, which is worse than that after primary stereotactic body radiotherapy. Reported rates of toxicity grade 3 or worse were considered acceptable. Larger target volume and central tumor localization were suggested as risk factors for severe toxicities. Dosimetric data on patients having toxicities were found to help with considering dose constraints for organs at risk. CONCLUSION: Based on data from a limited number of articles, salvage radiotherapy is a reasonable treatment option for select patients with local or regional tumor recurrence after prior stereotactic body radiotherapy for lung cancer. Optimal patient selection and dose prescription can be clarified with a larger study that include more data on experiences with salvage radiotherapy.